Revealing the relationships between alloy structure, composition and plastic deformation in a ternary alloy system by a combinatorial approach. (10th September 2021) - Lai, Jianping; Hu, Wen; Datye, Amit; Liu, Jingbei; Schroers, Jan; Schwarz, Udo D.; Yu, Jiaxin
Graphical abstract: Highlights: A high-throughput approach is used to establish a database of crystalline and amorphous alloys. The amorphous alloys exhibit a weaker compositional dependence in plasticity parameters. Different deformation mechanisms are responsible for respective plasticity behavior. A composition-dependent atomic model is proposed to elucidate structure-property relationships. Abstract: A high-throughput approach based on magnetron co-sputtering of alloy libraries is employed to investigate mechanical properties of crystalline and amorphous alloys in a ternary palladium (Pd)-tungsten (W)-silicon (Si) system with the aim to reveal the difference in plastic deformation response and extract the relevant structure-property relationships of the alloys in the system. It was found that in contrast to crystalline alloys, the amorphous ones, i.e., metallic glasses, exhibited a much smaller fluctuation range in the plasticity parameters ( E r 2 / H and W p / W t ), indicating a significant difference in the plastic deformation mechanism controlling the mechanical properties for the respective alloys. We propose that the inhomogeneous deformation of amorphous alloys localized in thin shear bands is responsible for the weaker compositional dependence of both plasticity parameters, while dislocation gliding in crystalline materials is significantly more dependent on the exact structure, thus resulting in a larger scattering range. Based on the representative efficient cluster packing model, a set of composition-dependent atomic structural models is proposed to figure out the structure-property relationships of amorphous alloys in Pd-W-Si alloy system.